Considerazioni sull’emersione della recidiva in età tardoantica - Beggiato, Martina (Tesserae iuris, 2023)
Although in the Roman legal experience there is no terminus technicus to qualify reiteration of crime, it can however be argued that the aggravation of punitive treatment as a consequence of falling back into crime was in any case known. Traces of this are also preserved in older sources, where reiterated delinquency is considered not only as an element of aggravation of the punitive treatment, but also as a cause of exclusion from the concession of indulgent measures. In fact, the legislator would have aimed at the offender’s repentance and social recovery through an emendatory function of the penalty. This was made possible by the spread of the Christian religion for which the recidivist would be a sinner to be redeemed, favouring his correction and re-education.